L’historiographie ou la « comédie de l’identité ». Une contribution à l’étude du concept de représentation en histoire à partir des réflexions de Michel de Certeau - Diana Napoli (Conserveries Mémorielles)
What does it mean to « represent » in history? This term has indeed a number of significations (referential movement that redirects to the past, performative practice, etc.) and it’s precisely this constitutive polysemy that allows it to be at the centre of discourse and of the « operation historiographique ». This polysemy can nevertheless be subjected to a more thorough examination thanks to the reflection of Michel de Certeau in a direction susceptible to demonstrate the almost “clinical” aspects that the historical “representation” is capable to mobilize in a society.Our goal is not to destabilize a central notion of the historiographical practice. Instead, we have tried to find, in the de Certeau’s work, a use of the concept of representation capable of interrogating the meaning of the historiographical act in a presentist regime of historicity in which, under the hold of the dimension of the presence, the historical and memorial discourses seem to confound themselves and to compete with each other in order to apprehend the past.Certeau has notably envisaged, from a reading of Freud, representation that history uses as a comedy of the identity that a society, in a relation an almost schizophrenic relation with the past, plays in order to establish itself in the present. It is from this aspect of the reflection of de Certeau that we have chosen to interrogate this time of the presence in which history seems deprived of the “past of the present” and always in more difficulty, possibly, in the act of representing itself the past.